Supply-side readiness to deliver HIV testing and treatment services in Indonesia: Going the last mile to eliminate mother-to-child transmission of HIV - Rabiah al Adawiyah; David Boettiger; Tanya L. Applegate; Ari Probandari; Tiara Marthias; Rebecca Guy; Virginia Wiseman (PLOS Global Public Health, 2022)
Introduction Despite national efforts to integrate Prevention of Mother-to-Child Transmission (PMTCT) of HIV services into antenatal care in Indonesia, the rate of mother-to-child transmission of HIV remains the highest in the world. A range of barriers to uptake and long-term engagement in care have been identified, but far less is known about health system preparedness to deliver PMTCT of HIV services. This study explored supply-side barriers to the delivery of PMTCT services in Indonesia and whether these factors are associated with the uptake of antenatal HIV testing. Materials and methods An ecological analysis was undertaken, linking data from the World Bank Quality Service and Delivery Survey (2016) with routine data from Indonesia’s HIV and AIDS case surveillance system and district health profile reports (2016). Supply-side readiness scores—generated from a readiness index that measures overall structural capacity and is often used as proxy for quality of care—were adapted from the WHO Service Availability and Readiness Assessment and presented by sector and geographic area. Univariate and multivariate regression analysis was used to explore factors associated with the uptake of antenatal HIV testing in public facilities. Results In general, public facilities scored more highly in most inputs compared to private facilities. Facilities located in urban areas also scored more highly in the majority of inputs compared to ones in rural areas. Readiness scores were lowest for PMTCT services compared to Antenatal Care and HIV Care and Support services, especially for the availability of medicines such as zidovudine and nevirapine. The national composite readiness score for PMTCT was only 0.13 (based on a maximum score of 1) with a composite score of 0.21 for public facilities and 0.06 for private facilities. The multivariate analysis shows that the proportion of pregnant women tested for HIV was more likely to be greater than or equal to 10% in facilities with a higher readiness score and a higher number of trained counsellors available, and less likely in facilities located outside of Java-Bali and in facilities supporting a higher number of village midwives. Discussion Despite targeted efforts by the Indonesian government and multinational agencies, significant gaps exist in the delivery of PMTCT that compromise the standard of care delivered in Indonesia. Future strategies should focus on improving the availability of tests and treatment, especially in the private sector and in rural areas.